High-resolution magnetic resonance imaging for predicting successful recanalization in patients with chronic internal carotid artery occlusion - Zhang, Xuan; Zhou, Chun; Cao, Yue-zhou; Su, Chun-qiu; Shi, Hai-bin; Lu, Shan-shan; Liu, Sheng (Frontiers in Neurology, 2022)
Abstract Objective: To investigate the predictive factors on high resolution magnetic resonance imaging (HR-MRI) for successful recanalization in patients with chronic internal carotid artery occlusion (CICAO). Methods: We included 41 consecutive patients who had CICAO and underwent recanalization attempts. The demographics, clinical data and HR-MRI features in relation to the technique success were collected and analyzed using univariate and multivariate analyses. A score-based prediction model was constructed by using a regression coefficient-based scoring method. Results: Technical success was achieved in 26 (63.4%) patients, with a complication rate of 12.2% (5/41). Based on multivariate analysis, occlusions involving ophthalmic artery segment (C6) or above (OR: 0.036; 95% confidence interval [CI], 0.04 to 0.336) and nontapered stump (OR: 0.064; 95% CI, 0.007 to 0.591) were identified as independent negative predictors for successful recanalization in patients with CICAO. Point scores were assigned according to the model coefficients, and the success rates of patient scored as 0,1 or 2 points were 93.33% (14/15), 66.67% (12/18), or 0% (0/8), respectively. Conclusion: HR-MRI characteristics maybe valuable in identifying candidates for endovascular recanalization in patients with CICAO. Occlusions involving C6 segment or above and nontapered stump were independent negative predictors for technical success.